Efektivitas Penambahan Sufentanil 10 mg pada Anestesi Epidural 15 mL Levobupivakain 0,5% untuk Tindakan Operasi Ekstremitas Bawah - Werda Laksana, Ngurah Putu; , Zulkifli; Harimin, Kusuma; , Theodorus (Perdatin Pusat, 2014)
Walaupun memiliki profil keamanan yang lebih baik daripada racemic, levobupivakain tetap memiliki mula kerja lambat dan lama kerja terbatas. Kombinasi opioid lipofilik sufentanil-levobupivakain akan memberikan efek sinergistik sehingga memperbaiki kekurangan tersebut, tetapi masih sedikit penelitian yang menilai kombinasi ini. Tujuan penelitian ini adalah untuk menilai efektivitas penambahan sufentanil 10 μg pada anestesi epidural levobupivakain 0,5% 15 mL dalam hal mula dan lama kerja blokade sensorik-motorik. Uji klinik randomized control trial (RCT) telah dilakukan terhadap 44 pasien (dibagi 2 kelompok; kelompok I (sufentanil 10 μg), kelompok II (2 mL NaCl 0,9%)) yang menjalani operasi ekstremitas bawah dengan anestesi epidural levobupivakain 0,5% di RSUP Dr. Mohammad Hoesin Palembang dari bulan Mei–Agustus 2013 yang memenuhi kriteria inklusi. Dilakukan penelitian terhadap mula, lama kerja blokade sensorik-motorik. Analisis data menggunakan SPSS® versi 20.0. Mula dan lama kerja blokade sensorik kelompok sufentanil secara statistik lebih bermakna daripada kelompok NaCl (p<0,001), sedangkan mula dan lama kerja blokade motorik tidak memiliki perbedaan bermakna secara statistik. Penambahan sufentanil 10 μg pada anestesi epidural levobupivakain 0,5% 15 mL mempercepat mula dan memperpanjang durasi kerja blokade sensorik. Kata kunci: Anestesi epidural, levobupivakain, sufentanil Although levobupivacaine has better safety profile than racemic bupivacaine, it has a slow onset of action and limited blockade duration. Combination of lipophilic opioid sufentanil-levobupivakain will provide synergetic effects that improve the shortcomings, but lack of research to support this. The aim of this study is to evaluate the efficacy of additional 10 μg sufentanyl to 15 mL 0.5% levobupivacaine epidural anesthesia toward sensory-motoric blockade onset and duration. Randomized controlled trials double blind study (RCT) has been conducted to 44 patients (divided into 2 groups : group I (sufentanil 10 μg), group II (2 mL NaCl0.9%)) underwent lower extremity surgery with epidural anesthesia 15 mL 0,5% levobupivakain in Dr. Mohammad Hoesin central hospital from May–August 2013 that met inclussion criteria. Onset and duration of action sensory-motoric blockade were studied. Data analysis using SPSS® version 2.0. The onset and the duration of sensory blockade in sufentanil group is statistically significant than NaCl group (p<0.001). However the onset and duration of motoric blockade are not statistically significant. The addition of 10 μg sufentanil to 15 mL of 0.5% levobupivacaine epidural anesthesia hasten the onset and prolong the duration of sensory blockade. Key words: Epidural anesthesia, levobupivacaine, sufentanyl Reference Bajwa SJS, Kaur J. Clinical profile of levobupivacaine in regional anesthesia: a systematic review. J Anaesth Clin Pharmaco. 2013;29:530–9. Burlacu CL, Buggy DJ. Update on local anesthetics: focus on levobupivacaine. Therapeutics and Clinical Risk Management. 2008;4(2):381–92. Casimiro C, Rodrigo J, Mendiola MA, Rey F, Barrios A, Gilsanz F. dkk. Levobupivacaine plus fentanyl versus racemic bupivacaine plus fentanyl in epidural anaesthesia for lower limb surgery. Minerva Anestesiol. 2008;74:381–91. Liu SS, Lin Y. Local Anesthetics. Dalam: Barash PG, Cullen, Cullen BF, Stoelting RK, Cahalan MK, Stock MC, penyunting. Clinical anesthesia. Edisi ke-6. Philadelphia: Lippincott Williams & Wilkins; 2009. hlm. 531–48. Leone S, Cianni SD, Casati A, Fanelli G. Pharmacology, toxicology, and clinical use of new long acting local anesthetics, ropivacaine and levobupivacaine. Acta Biomed. 2008;79:92–105. Khangure N. Adjuvant agents in neuroaxial blockade [document on the internet]. Western Australia: World Federation of Societies of Anaesthesiologist; 2011 [diperbarui tanggal 2011 July 4; diunduh 1 Februari 2013]. Tersedia dari: http://www.totw. anaesthesiologists.org. Kaur M. Adjuvants to local anesthetics: a combination wisdom. Anesth Essays Res. 2010:4;122–3. Christiansson L. Update on adjuvants in regional anaesthesia. Periodicum Biologorum. 2009;111:161–70. Yeerdaoolaiti Y, Long W, Jian-Hua DU. Clinical effect of sufentanil combined with ropivacaine used in epidural anesthesia for abdominal hysterectomy. Modern Preventive Medicine. 2011;19:4096–103. Bachman-Mennenga B, Veit G, Stenicke B, Biscoping J, Heesen M. Efficacy of sufentanil addition to ropivacaine epidural anaesthesia for caesarean section. Acta Anaesthesiol Scand. 2005;49:532–7. Bachman-Mennenga B, Veit G, Biscoping J, Stenicke B, Heesen M. Epidural ropivacaine 1% with and without sufentanil addition for caesarean section. Acta Anaesthesiol Scand. 2005;49:525–31. Prabowo RSE. Pengaruh penambahan fentanil 1,5 μg.kg1 pada ropivakain 0,75% terhadap mula dan lama kerja blokade anestesi epidural untuk operasi ekstermitas bawah. Dokter Spesialis Anestesi [Tesis]. Bandung: Universitas Padjajaran; 2004. Macres SM, Moore PG, Fishman SM. Acute pain management. Dalam: Barash PG, Cullen, Cullen BF, Stoelting RK, Cahalan MK, Stock MC, penyunting. Clinical anesthesia Edisi ke-6. Philadelphia: Lippincott Williams & Wilkins; 2009. hlm. 1473–1504. NYSORA. Epidural Blockade [document on the internet]. New York: New York School of Regional Anesthesia; 2009 [diperbarui tanggal 2009 January 3; diunduh 1 Februari 2013]. Tersedia dari http://www.nysora.com. Pain Community Centre. Epidural: the mode of action of local anaesthetics and opioids in the epidural. Wales: Cardiff University; 2012[diunduh 1 Februari 2013]. Tersedia dari: http://www.paincommunitycentre.org. Vora KS, Shah VR, Patel B, Parikh GP, Butala BP. Postoperative analgesia with epidural opioids after cesarean section: Comparison of sufentanil, morphine and sufentanil-morphine combination. J Anaesth Clin Pharmaco. 2012;28:491–5. Visser WA, Lee RA, Gielen MJM. Factors affecting the distribution of neural blockade by local anesthetics in epidural anesthesia and a comparison of lumbar versus thoracic epidural anesthesia. Intern Anesth Research Soc. 2008;107(2):708–21. Staahl C, Olesen AE, Andreses T, Arendt- Nielsen L, Drewes AM. Assesing analgesic actions of opioids by experimental pain models in healthy volunteers-an updated review. Bri J Clin Pharmaco.2009;68(2):49–68. George MJ. The site of action of epidurally administered opioids and its relevance to postoperative paint management. Anaesthesia. 2006;61:659–64. Veering BT, Cousins MJ. Epidural neural blockade. Dalam: Cousins MJ, Bridenbaugh PO, penyunting. Neural blockade in clinical anesthesia and management of pain Edisi ke-4. Philadelphia: Lippincott–Raven Publishers; 2008. hlm. 241–95.